2019
DOI: 10.1158/1078-0432.ccr-18-1294
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ACKR2-Dependent Role of Fibroblast-Derived CXCL14 in Epithelial-to-Mesenchymal Transition and Metastasis of Breast Cancer

Abstract: Purpose: Fibroblasts expressing the orphan chemokine CXCL14 have been previously shown to associate with poor breast cancer prognosis and promote cancer growth. This study explores the mechanism underlying the poor survival associations of stromal CXCL14. Experimental Design: Tumor cell epithelial-to-mesenchymal transition (EMT), invasion, and metastasis were studied in in vitro and in vivo models together with fibroblasts overexpressing CXCL14. An approach for CXCL14 receptor identification included loss-of-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 59 publications
1
65
0
Order By: Relevance
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…20 The EMT entails tumor cells loosing surface contact and epithelial physiognomies during early metastasis phases, acquiring mesenchymal traits instead, which facilitates surrounding tissue invasion and metastasis. 21 During PC progression, epithelial cells undergo the EMT, characterized by morphological changes in their phenotype from cuboidal to spindle-shaped. 22 Epithelial cells predominantly express E-cadherin, whereas N-cadherin is a mesenchymal protein.…”
Section: Discussionmentioning
confidence: 99%
“…eMT is a vital mechanism during cell growth, tissue repair and organ fibrosis (9); however, it is also closely associated with tumor invasion and migration (53). Previous studies have demonstrated that via the eMT process, cells gain invasive and anti-apoptotic abilities (10)(11)(12)54). The hallmark changes of eMT include a reduction in intercellular adhesion and a loss of cell polarity (55).…”
Section: Discussionmentioning
confidence: 99%
“…during eMT, epithelial cells lose cell adhesions and undergo cytoskeletal alterations (11). in breast cancer, eMT is associated with local invasion and migration, and is marked by the loss of epithelial properties and the acquisition of mesenchymal properties (12). Previous studies demonstrated that a variety of factors can induce eMT, including transforming growth factor β (TGF-β), Wnt, Notch and fibroblast growth factor (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%